Arsenic Transfer from As-Rich Sediments to River Water in the Presence of Biofilms - Diego Martiñá Prieto; Verónica Martín-Liñares; Verónica Piñeiro; María Teresa Barral (Journal of Chemistry)
The influence of epipsammic biofilms on As release from river sediments was evaluated in a microcosm experiment where biofilms were grown on sediments containing 106 mg kg−1 As, collected in the Anllóns River, and compared with control systems without biofilms. The As transfer to the water column was low (<0.11% of total As in the sediment) and was further reduced by 64% in the presence of biofilms. AsV was the predominant species in the overlying water in both systems. AsIII concentration was higher (up to 12% of total dissolved As) in the control systems than in the systems with biofilms, where this species was almost absent. This fact is of toxicological relevance due to the usually higher mobility and toxicity of the reduced AsIII species. Control systems exhibited higher As mobility in water, in sulphate solution, and in weak acid medium and higher bioavailability in diffusive gradient in thin films (DGT) devices. Arsenic retained by the biofilm was equally distributed between extracellular and intracellular compartments. Inside the cells, significant concentrations of AsIII, monomethylarsonic acid (MMAV), and dimethylarsinic acid (DMAV) were detected, suggesting that active methylation (detoxification) processes are occurring in the intracellular compartment.